Fundamental effective temperature measurements for eclipsing binary stars – III. SPIRou near-infrared spectroscopy and CHEOPS photometry of the benchmark G0V star EBLM J0113+31. Issue 4 (16th May 2022) - Maxted, P F L; Miller, N J; Hoyer, S; Adibekyan, V; Sousa, S G; Billot, N; Fortier, A; Simon, A E; Collier Cameron, A; Swayne, M I; Gutermann, P; Triaud, A H M J; et al.
ABSTRACT: EBLM J0113+31 is a moderately bright ( V = 10.1), metal-poor ([Fe/H] ≈−0.3) G0V star with a much fainter M dwarf companion on a wide, eccentric orbit (= 14.3 d). We have used near-infrared spectroscopy obtained with the SPIRou spectrograph to measure the semi-amplitude of the M dwarf's spectroscopic orbit, and high-precision photometry of the eclipse and transit from the CHEOPS and TESS space missions to measure the geometry of this binary system. From the combined analysis of these data together with previously published observations, we obtain the following model-independent masses and radii: M 1 = 1.029 ± 0.025 M⊙, M 2 = 0.197 ± 0.003 M⊙, R 1 = 1.417 ± 0.014 R⊙, R 2 = 0.215 ± 0.002 R⊙ . Using R 1 and the parallax from Gaia EDR3 we find that this star's angular diameter is θ = 0.0745 ± 0.0007 mas. The apparent bolometric flux of the G0V star corrected for both extinction and the contribution from the M dwarf (<0.2 per cent) is F_, 0 = (2.62± 0.05)× 10^-9 erg cm −2 s −1 . Hence, this G0V star has an effective temperature T_eff, 1 = 6124 K ± 40 K (rnd.) ± 10 K (sys.) . EBLM J0113+31 is an ideal benchmark star that can be used for 'end-to-end' tests of the stellar parameters measured by large-scale spectroscopic surveys, or stellar parameters derived from asteroseismology with PLATO . The techniques developed here can be applied to many other eclipsing binaries in order to create a network of such benchmark stars.